The Impact of Nero Book Series on Inclusive-Collaborative Parenting in ECE - Armelia, Salsa; Mirawati, Mirawati; AM, Muh Asriadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research in based on a problem where teachers and parents do not yet know what Neurodivergent and Inclusive-Collaborative parenting are. This research aims to obtain test result on the implementation of the Nero Books series on Teachers and Parents in improving Inclusive-Collaborative Parenting in TK Labschool UPI Cibiru. This research uses a case study method with observation and interview data collection techniques. Data was collected and analyzed using Miles and Huberman data analysis starting from data collection, data presentation and concluding. The Results show that the Nero Book Series significantly increases teachers' and parents' understanding of Neurodivergent children, supporting more effective collaboration in inclusive-collaborative parenting. This is based on interviews conducted by researchers with teachers and parents who saw changes for the better. So this Nero book series has succeeded in creating inclusive, collaborative parenting that is synergistic for teachers and parents.